TO DETERMINE THE EFFECTIVENESS OF PATIENT EDUCATION AND COUNSELLING AS A SELF-LEARNING STRATEGY FOR UNDERGRADUATE MEDICAL STUDENTS - Gabeen, Humera; Mahboob, Usman; Adeeb, Humera; Jamil, Brekhna; Imtiaz , Hajra; Asim, Nowshad (Journal of Ayub Medical College Abbottabad, 2024)
Background: Patient education and counselling is an effective strategy for fostering patient-doctor relationship. Undergraduate medical students must learn how to counsel patients. Objectives were to assess the effectiveness of patient education and counselling as a teaching strategy and compare it with the Large Group interactive teaching strategy (LGIS). Methods: A true experimental study was conducted at Saidu Medical College affiliated hospital with 60 fourth-year MBBS students. Stratified random sampling divided participants into control (LGIS) and experimental (self-learning with patient counselling) groups. Both groups took a baseline knowledge test. The control group attended lectures, while the experimental group studied self-care for type 2 diabetes and conducted patient counselling with a simulated patient. Post-intervention knowledge scores and feedback were analyzed using SPSS 23. Results: The LGIS group pre-test mean baseline knowledge score was 30.73±12.11, increasing to 35.40±13.29 post-test. The experimental group, pre-test and post-test knowledge scores ±SD were 31.67±12.75 and 38.95±12.95 respectively. Paired t-tests showed significant improvements in both groups with a p-value of 0.001. However, the independent t-test indicated no significant difference between the two teaching methods (p=0.299). Additionally, 90% of the experimental group found patient counselling techniques practical and effective. Conclusion: Although significant associations between the two groups were not observed, effective patient counselling is a more practical learning technique to understand diseases in clinical settings.